2008
DOI: 10.1007/s12253-008-9132-y
|View full text |Cite
|
Sign up to set email alerts
|

Expression of EphA2 and E-cadherin in Gastric Cancer: Correlated with Tumor Progression and Lymphogenous Metastasis

Abstract: In this study, gastric cancer progression was correlated with the over-expression of erythropoietin-producing hepatocellular (Eph)A2 receptor and down-expression of epithelial cadherin (E-cadherin). Immunohistochemistry of EphA2 and E-cadherin were performed on these tumor samples from 165 primary lesions of gastric cancer. The results showed that expression of EphA2 was obviously increased in gastric cancer tissues (P < 0.01), which was positively correlated with the depth of cancer invasion, tumor-node-metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 33 publications
3
29
1
Order By: Relevance
“…Although the most comprehensive data so far demonstrated that Eph-A2 was associated with important clinicopathological characteristic for patients' management in a variety of malignant tumors [23,26,[28][29][30][31][32][33][34][35][36][37][38][39], we did not find any clinical significance of Eph-A2 in pancreatic neoplasia except for a trend of correlation with patients' age. Moreover, Eph-A2 overexpression was significantly associated with poor prognosis in several types of malignant tumors, including that of oral tongue, as well as oesophageal, lung, cervical, ovarian, endometrial and renal carcinoma, as well as glioblastoma [26,29,33,36,[38][39][40][41].…”
Section: Discussioncontrasting
confidence: 78%
“…Although the most comprehensive data so far demonstrated that Eph-A2 was associated with important clinicopathological characteristic for patients' management in a variety of malignant tumors [23,26,[28][29][30][31][32][33][34][35][36][37][38][39], we did not find any clinical significance of Eph-A2 in pancreatic neoplasia except for a trend of correlation with patients' age. Moreover, Eph-A2 overexpression was significantly associated with poor prognosis in several types of malignant tumors, including that of oral tongue, as well as oesophageal, lung, cervical, ovarian, endometrial and renal carcinoma, as well as glioblastoma [26,29,33,36,[38][39][40][41].…”
Section: Discussioncontrasting
confidence: 78%
“…Selective inhibition of MET is known to kill MET-overexpressing gastric cancer cells effectively [14,46] and is the rationale for ongoing clinical trials of MET inhibitors for gastric cancer therapy. Our data also showed overexpression of several genes whose protein products were phosphorylated and have been proposed as useful prognostic markers and/or therapeutic targets for gastric cancer, including EGFR [47], TOP2A [48], minichromosome maintenance 2 (MCM2) [49], erythropoietin-producing hepatocellular (Eph) A2 receptor [50], CTNNB1 [51] and hepatoma-derived growth factor (HDGF) [52]. The data sets also reveal novel overexpressed and phosphorylated proteins whose roles in gastric cancer have yet to be defined, such as EIF2S3, LMNB2, KIF23, SLC7A5/CD98 and MCM3 (supplemental Table 9), although some have been associated with other types of cancers.…”
Section: Discussionmentioning
confidence: 57%
“…Interestingly, at EphB/ephrinB epithelial boundaries ADAM10 sheds colocalised E-cadherin, allowing segregation of the two cell populations while relative adhesiveness within the populations is increased [254]. Thus, de-regulated Eph-cadherin crosstalk might contribute to the tumorigenic potential of Eph/ephrin-positive cancer cells through alterations of cell-cell adhesion [255,256].…”
Section: Eph-regulated Adhesion Dynamicsmentioning
confidence: 99%